2012
DOI: 10.1080/13546805.2012.670504
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive beliefs and psychological well-being in paranoia and depression

Abstract: These findings suggest that psychological well-being is particularly compromised in participants with a high level of persecutory thinking when they have low levels of cognitive self-consciousness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 56 publications
2
15
0
Order By: Relevance
“…On the other hand, patients had experienced on average three depressive episodes and were hospitalized for the second time 10 , which may indicate that their current depressive symptoms might have underplayed the general severity of their disorder. Moreover, scores of the assessed MCQ subscales were largely comparable to those of other, more severely depressed patients 2830 .…”
Section: Discussionmentioning
confidence: 55%
“…On the other hand, patients had experienced on average three depressive episodes and were hospitalized for the second time 10 , which may indicate that their current depressive symptoms might have underplayed the general severity of their disorder. Moreover, scores of the assessed MCQ subscales were largely comparable to those of other, more severely depressed patients 2830 .…”
Section: Discussionmentioning
confidence: 55%
“…One explanation is the influence of cognitive process variation in schizophrenia and affective disorders like depression. Valiente et al (2012) reported difference in metacognitive beliefs in paranoia and depression that relate to their perception of psychological well-being where “individuals with paranoia use self-consciousness (defined as the process of directing attention towards the self) to monitor self-threats” [ 47 , 48 ]. The study found low psychological well-being in the domains of self-acceptance and autonomy in depression versus those with persecution delusions and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…However, given that negative beliefs about the self were not implicated in paranoid conviction in the present sample, it might be argued that they should not be the first target of intervention. A complication, already noted, is that self-esteem may fluctuate rapidly in paranoid patients (Thewissen et al 2008;Udachina et al 2012) and it has also been noted that implicit selfesteem may be affected in paranoid patients even when explicit self-esteem (as measured by questionnaire) is not (Valiente et al 2012).…”
Section: Discussionmentioning
confidence: 99%